2017
DOI: 10.1021/acschembio.7b00125
|View full text |Cite
|
Sign up to set email alerts
|

NHS-Esters As Versatile Reactivity-Based Probes for Mapping Proteome-Wide Ligandable Hotspots

Abstract: Most of the proteome is considered undruggable, oftentimes hindering translational efforts for drug discovery. Identifying previously unknown druggable hotspots in proteins would enable strategies for pharmacologically interrogating these sites with small molecules. Activity-based protein profiling (ABPP) has arisen as a powerful chemoproteomic strategy that uses reactivity-based chemical probes to map reactive, functional, and ligandable hotspots in complex proteomes, which has enabled inhibitor discovery aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(169 citation statements)
references
References 35 publications
5
150
1
1
Order By: Relevance
“…In addition, to further test the proteome-wide selectivity for KEA1–97, we also performed isoTOP-ABPP studies competing KEA1–97 against our recently disclosed NHS-ester-alkyne reactivity-based probe. 10 Interestingly, while this probe identified >1000 probe-modified lysines in 231MFP cells, compared to the 80 lysines profiled by the DCT-alkyne probe, we did not identify K72 of TXN. Rather, the NHS-ester-alkyne probe labeled K94 of TXN which showed an isotopically light to heavy ratio of 1.0, indicating that this site was not a target of KEA1–97.…”
contrasting
confidence: 63%
“…In addition, to further test the proteome-wide selectivity for KEA1–97, we also performed isoTOP-ABPP studies competing KEA1–97 against our recently disclosed NHS-ester-alkyne reactivity-based probe. 10 Interestingly, while this probe identified >1000 probe-modified lysines in 231MFP cells, compared to the 80 lysines profiled by the DCT-alkyne probe, we did not identify K72 of TXN. Rather, the NHS-ester-alkyne probe labeled K94 of TXN which showed an isotopically light to heavy ratio of 1.0, indicating that this site was not a target of KEA1–97.…”
contrasting
confidence: 63%
“…Alternative electrophiles, when used as broad profiling probes, may also provide access to additional lysine residues in the proteome, although the chemoselectivity of such probes could present a challenge. While our manuscript was under review, for instance, Ward and colleagues characterized the proteomic reactivity of an NHS-ester probe and found that, while this activated ester labeled lysines, it also showed substantive reactivity with several other amino acid residues (serine, threonine, tyrosine, arginine, cysteine) across the mouse liver proteome 61 . These results are consistent with our initial gel-based profiling experiments studies of a similar NHS ester probe ( 8 ), which showed substantially higher overall proteomic reactivity compared to the STP probe 1 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…32 The mAb-alkyne was used to demonstrate this analytical approach, illustrated in Figure 1. Lysine or primary amine conjugation in a mAb is highly heterogeneous due to the more than eighty lysine residues, making detection of the conjugation site quite challenging.…”
Section: Methodsmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39] Detection of alkynes is of great significance due to its broader applications and coupling with click chemistry. However, since the 1.2.3-triazole product often lacks specific properties, the detection becomes challenging especially with heterogeneous protein modifications, in vivo sample matrices and low abundant protein samples.…”
Section: Alkyne Modificationsmentioning
confidence: 99%
See 1 more Smart Citation